2010
DOI: 10.1016/j.ijpara.2010.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant cryptosporidiosis associated with digestive adenocarcinoma in SCID mice infected with Cryptosporidium parvum TUM1 strain

Abstract: Graphical Abstract Click here to download high resolution image 1 RAPID COMMUNICATIONWe demonstrated recently that Cryptosporidium parvum IOWA strain induces in situ ileo-caecal 4 adenocarcinoma in an animal model. Herein, the ability of another C. parvum strain and other 5Cryptosporidium species to induce digestive neoplasia in dexamethasone-treated SCID mice was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 19 publications
3
48
2
1
Order By: Relevance
“…Additionally, the results of this study showed for the first time the ability of an isolate of C. parvum of human origin to cause gastrointestinal and biliary adenocarcinomas in an experimental model, providing supplementary evidence of a direct role of this parasite in the induction of digestive cancer (4)(5)(6). Furthermore, these findings demonstrate that C. parvum-induced neoplasia is an invasive process that can evolve rapidly in immunosuppressed hosts.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Additionally, the results of this study showed for the first time the ability of an isolate of C. parvum of human origin to cause gastrointestinal and biliary adenocarcinomas in an experimental model, providing supplementary evidence of a direct role of this parasite in the induction of digestive cancer (4)(5)(6). Furthermore, these findings demonstrate that C. parvum-induced neoplasia is an invasive process that can evolve rapidly in immunosuppressed hosts.…”
Section: Discussionsupporting
confidence: 55%
“…However, in this report it was unclear whether C. parvum behaved as a carcinogenesis factor or simply as an opportunistic agent whose development was enhanced by host immunosuppression. More consistent with a potential tumorigenic role of this parasite, we recently showed that IOWA and TUM1 strains of C. parvum of animal origin induced digestive neoplasia in a rodent model (4)(5)(6). We report herein the first evidence of the ability of a human-derived C. parvum strain to induce gastrointestinal cancer in mice.…”
supporting
confidence: 75%
See 3 more Smart Citations